Measurement and Analysis of Roadway Deformation and Stress under Mining-Induced Stress - Jianfeng Cui; Weijun Wang; Qian Jia; Gang Peng; Hai Wu (Shock and Vibration)
Small coal pillars, which are used to protect roadways, have a significant influence on mining operations and roadway stability and safety. Consequently, the optimal width of coal pillars that provides suitable performance under mining-induced stress must be determined accurately. Based on the deformation data of the surrounding rock along the gob roadway of the 13318 working face in Xieqiao Coal Mine, we analyzed the surface deformation data of the roadway and the displacement of the deep surrounding rock of the roadway under the action of mining-induced stress herein. The separation fractures of the low side of the roadway can be divided into four zones: 0–2 m, 2–5 m, 5–9 m, and 9–11 m. The absolute displacement of the surrounding rock relative to the center of the roadway in the 0–2 m zone was large, and the displacement region in the side of the roadway extended from 0 m to 11 m. The separation fractures of the high side of the roadway can be divided into three zones: 0–3 m, 3–5 m, and 5–5.5 m. The absolute displacement of the surrounding rock relative to the center of the roadway in the 0–3 m zone was large, whereas the deformation separation of the coal pillar was small. The surrounding rock in the 5–5.5 m zone also exhibited absolute displacement relative to the center of the roadway. Furthermore, the stress increased faster on the low side of the roadway than the high side; the core stress region on the high side occurred at approximately 3 m, whereas that on the low side occurred at approximately 8 m. The findings obtained herein can help determine the optimal preset width of small pillars.